Pengentasan Kemiskinan dan Peningkatan Kesejahteraan Masyarakat melalui Optimalisasi Peran Zakat, Infaq, dan Shadaqah: Pengabdian kepada Masyarakat di Kelurahan Mekarsari, Kota Banjar - Sumarni, Sumarni; Husaini, Fauzan; Yuniartin, Titin; Aziz, Deris Syahrul; Fitriani, Ratna Dewi; Fiqriyanti, Dida Amala (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2022)
This study discusses the role of zakat, infaq, and shadaqah (ZIS) in alleviating poverty and improving the welfare of the community in Kelurahan Mekarsari, Kecamatan Banjar, Kota Banjar. ZIS, as an important part of philanthropy in Islam, not only fulfills religious obligations but also contributes significantly to the socio-economic aspects of society. Using a qualitative descriptive method, this study highlights how BAZNAS Kota Banjar effectively manages and distributes ZIS funds. Through outreach and seminars organized by BAZNAS, the community of Kelurahan Mekarsari is educated on the benefits and importance of ZIS. This activity aims to provide knowledge about the role of ZIS in alleviating poverty and improving welfare, targeting active members of the mosque and RW leaders. Assistance is provided through seminars using a question-and-answer method. The study's results indicate that active participation in ZIS can significantly reduce poverty levels and improve community welfare, particularly through economic empowerment programs run by BAZNAS Banjar City.